Educação cientifica e questões étnico-raciais: uma proposta intercultural para o ensino de química no nível médio - Moreno, Ingrid dos Santos Souza (Brasil, 2024)
Although Law 10,639 was published in 2003, making it mandatory to teach African and Afro- Brazilian history and culture content in public and private education, even today Ethnic-Racial Issues (QER) are barely present in schools and research. in Chemistry Teaching (EQ). Thus, the objective of this research was to investigate the potential of applying a didactic sequence with the QER approach in Chemistry classes in a 3rd year high school class at a public school in the city of Itacoatiara-AM. The research is qualitative in nature and involved the participation of 22 high school students. Three didactic sequences were conducted, each accompanied by an activity sheet containing essay questions (open). aiming to identify students' perceptions regarding the topics discussed during the study. The results made it clear that the introduction of teaching materials during classes plays a crucial role, as it arouses students' interest in actively participating. Therefore, the generating themes used proved to be effective tools for social thematic contextualization, thus contributing to more meaningful student engagement.